Natural Gas Extraction, Earthquakes and House Prices - Hans R.A. Koster; Jos N. van Ommeren (Tinbergen Institute, 2015)
The production of natural gas is strongly increasing around the world. Long-run negative external effects of extraction are understudied and often ignored in social) cost-benefit analyses. One important example is that natural gas extraction leads to soil subsidence and subsequent induced earthquakes that may occur only after a couple of decades. We show that induced earthquakes that are noticeable to residents generate substantial non-monetary economic effects, as measured by their effects on house prices, also when house owners are fully compensated for damage to their houses. To address the issue that earthquakes do not occur randomly over space, we use temporal variation in the occurrence of noticeable earthquakes while controlling for the occurrence of earthquakes that cannot be felt by house owners. We find that earthquakes that are noticeable with peak ground velocities of above half a cm/s lead to price decreases of 1.2 percent. The total non-monetary costs of induced earthquakes for Groningen are about 150 million, about 500 per household. The results also indicate that the non-monetary costs of are in the same order of magnitude as the monetary damage costs.
Keywords: Q54; Q32; R30; R33; 330; natural gas extraction; earthquakes; house prices; hedonic price analysis